2014
DOI: 10.19030/jier.v10i2.8516
|View full text |Cite
|
Sign up to set email alerts
|

Adoption Of Social Networking In Education: A Study Of The Use Of Social Networks By Higher Education Students In Oman

Abstract: The use of social networks is a growing phenomenon, being increasingly important in both private and academic life. Social networks are used as tools to enable users to have social interaction. The use of social networks (SNs) complements and enhances the teaching in traditional classrooms. For example, YouTube, Facebook, wikis, and blogs provide a huge amount of material on a wide range of subjects. This research aims to explore the need to change the traditional style of teaching and learning after the innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 25 publications
2
44
0
1
Order By: Relevance
“…According to Lange-Faria and Elliot (2012), social media refers to Internet applications that allow their users to create, share and consume User-Generated Content. In addition, it gives people the ability to communicate and share their interests and personal information with others from all around the world Al-Mukhaini et al, 2014).…”
Section: Social Media Definitionmentioning
confidence: 99%
“…According to Lange-Faria and Elliot (2012), social media refers to Internet applications that allow their users to create, share and consume User-Generated Content. In addition, it gives people the ability to communicate and share their interests and personal information with others from all around the world Al-Mukhaini et al, 2014).…”
Section: Social Media Definitionmentioning
confidence: 99%
“…Si en la etapa educativa obligatoria en muchas ocasiones el rol del docente y el de la comunidad educativa ha de centrarse en el control y la limitación del uso de las redes sociales, en el ámbito universitario los esfuerzos habrán de dirigirse en la búsqueda de estrategias metodológicas y evaluativas que favorezcan su utilización (Al-Mukhaini, Al-Qayoudhi, & Al-Badi, 2014). No se trata de abordar la enseñanza de su uso, sino de enfocar su trabajo como medio en la difusión, tratamiento y profundización de los contenidos que se abordan en clase (García & Martín, 2013).…”
Section: Introductionunclassified
“…Some [12] studied the use of social networking sites by undergraduates, graduates, and faculty members at Yonsei Institution in Seoul, South Korea and [9] found that the youths at age group of 13-14 years based on gender, ethnicity and parental income, were using social networking sites more than at age group of 20-23 years. There have been studies on social media in higher education in different countries like in Oman [1], Dublin [14], USA [4].…”
Section: Related Workmentioning
confidence: 99%